Evidence on ecological dynamics and constraints-led coaching in tennis: a systematic review of skill acquisition, performance, and technology integration - Andre Igoresky; Mario Febrian; Ifdil Ifdil (Lentera Negeri, 2026)
The study reviewed a body of research on the effects of Ecological Dynamics and the Constraints-Led Approach (CLA) in tennis coaching, looking for a pattern of evidence. Using Scopus and following PRISMA 2020, the systematic review identified peer-reviewed English-language articles published in the period of 2018-2026 that focused on ecological theories, constraints-led approach to physical education and coach development through representative learning, or technologies for tennis practice. From the 238 records we screened, we found 10 articles that fit the inclusion criteria to be the focus of this work and we used thematic analysis method for summarizing their findings. The quality of the methods used in the included studies was assessed using the FICO framework, which helped us identify a variety of strengths and weaknesses that characterized this research area. Overall, the results show that representative learning design together with manipulation of various constraints (task or environmental) brought consistent improvement in skill execution, perception-action attunement, decision-making and match performance. Besides that, technologies such as wearable devices, virtual reality and machine learning have proven to be valuable tools in terms of measuring performance objectively and delivering representative feedback. Still, there are some limitations on the existing literature that may affect the credibility of the reported findings including low number of participants, predominantly adolescents as experimental subjects of the research, and using only one electronic database to retrieve the records.